Pengaruh Biaya Produksi dan Biaya Operasional Terhadap Laba Bersih Pada PT. Wilmar Cahaya Indonesia, Tbk. Tahun 2007-2023 - Merlin Ghardanova (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
The purpose of this study was to determine the effect of production costs and operating costs on net income both partially and simultaneously at PT Wilmar Cahaya Indonesia, Tbk 2007-2023. The research method used is associative method, through secondary data collection with library studies of financial reports for 17 years from2007 to 2024, using multiple linear regression analysis, correlation analysis, t test and f test. The results of this study indicate that partially production costs have a significant effect on net income with a t test result value of 3,632, partially operational costs have no significant effect on net income with a t test result value of -1,024, andsimultaneously production costs and operational costs affect net income with a f test result value of 18,397.